An Overview of Aspects of Sustainability in The Business Environment - Mária Demjanovičová; Dominika Tumová (Communications of International Proceedings, 2021)
The article provides an overview of approaches to solving sustainability in business practice. Communication of companies with customers and perceived parameters of communicated values. The attitude of companies to the problem is changing due to a change in customer behaviour. Businesses perceive the importance of sustainability in business and plan to implement these activities in their business models in the future. The aim of this article is to provide a topical overview of the issue of sustainability and its impacts on local business-making in Slovakia – managerial skills. The article focuses on the impact of the pressing questions of sustainability on the business environment in the sector of micro and small businesses. Via a thorough analysis of the theoretical foundations in the field of sustainability, the article provides an overview of the approaches to its application into practice as well as the theoretical determination of the term itself, with its different directions. The theoretical foundations of the article are based on the approach of Chernev and Blair who brought a controversial outlook on the elements of sustainability understood as marketing actions are taken to capture the attention of the customer. This attitude emphasizes the question of how to declare true sustainability and not just use the positive impacts of this term. The article provides a basic specification of sustainability value parameters and how to implement them in the business models of small and medium enterprises. It serves as an overview of the current situation in the field of sustainability and approaches to its implementation in micro-enterprises by specific naming of sustainability value parameters and their specification.